EXTRACTION-PHOTOMETRIC DETERMINATION OF ANALGINUM BY FUCHSINE IN PHARMACEUTICALS (Proceedings of the YSU B: Chemical and Biological Sciences, 2009)
Interaction of analginum anion with triphenilmethane (TPM) basic dye fuchsine has been studied. The colored ionic associate (IA) could be extracted by dichlorethane–acetone (2:1) binary mixture in pH 2 (H2SO4) solutions. The range of determined concentration of analginum is             7.11·10-5–1.423·10-3 M, of fuchsine is 4.44·10-4–1.04·10-3 M . A attitude of components in IA is 1:1. The elaborated method has been applied for determination of analginum in pentalgin-H, spasmalgonum, spasgan. In the case of tempalgin low results are received. Fuchsine is less sensitive, than earlier reported methods by other TPM dyes.
Keywords: analginum; triphenilmethane; ionic associate; determination of analginum